Citizen Seismology Without Seismologists? Lessons Learned From Mayotte Leading to Improved Collaboration - Fallou, Laure; Bossu, Rémy; Landès, Matthieu; Roch, Julien; Roussel, Frédéric; Steed, Robert; Julien-Laferrière, Sylvain (Frontiers in Communication, 2020)
Starting the 10th May 2018, a series of earthquakes has hit Mayotte, a French island in the Indian Ocean. Facing a lack of seismic data, scientific information and communication from the authorities, the inhabitants took advantage of social media to develop, on their own, a citizen seismology group, composed of more than 10 000 people. Due to a particular cultural context, this was carried out mainly without the seismologist community. While some citizens did share seismological information (and eventually volcanology information when it was discovered that the earthquakes were caused by a new-born, undersea volcano), the lack of seismologists in the group also lead to the emergence of misinformation and even conspiracy theories. This mistrusting atmosphere had negative consequences for the way various seismological organisations were perceived, including LastQuake, a crowdsourced-based earthquake information app which allows eyewitnesses to share information about earthquakes they felt, combined with seismic data. However, due to the lack of seismic data for these earthquakes, some were not displayed in the app. This lack of information and understanding of how the system functioned led to additional mistrust towards this citizen seismology tool. This paper combines sociological observations with an empirical approach. First, a sociological analysis of this independent citizen science network enables an identification of the reasons for its creation and the pitfalls caused by the absence of collaboration with the scientific community. Then, an empirical case study of the LastQuake system exposes how it has been improved to offer information, while admittedly more incomplete, is nevertheless closer to citizens’ needs. It concludes that citizen seismology requires a stronger collaboration between citizens’ and scientists’ communities in order to be more efficient. It also advocates for scientific communication that takes into account cultural context from the beginning.